ASSESSMENT OF UNIVERSAL COMPETENCIES OF STUDENTS - Medvedeva, Irina; Martynyuk, Oxana; Pan’kova, Svetlana; Solovyova, Irina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Assessing the competencies of students is an important and challenging task. The article presents the experience of evaluating the universal competencies of students. We created individual and group exercises, criteria for evaluating the results of these exercises for assessing the universal competencies of students. In addition to expert evaluation, students were interviewed to identify their self-esteem. The created assessment tools were used for several years at the Faculty of Physics and Mathematics of the Pskov State University to assess the universal competencies of first year students (more than 200 students participated). Some research results are analyzed in the article.